Theoretical Understanding of Polar Topological Phase Transitions in Functional Oxide Heterostructures: A Review. Issue 9 (28th July 2022) - Guo, Xiangwei; Zhou, Linming; Roul, Basanta; Wu, Yongjun; Huang, Yuhui; Das, Sujit; Hong, Zijian
Abstract: The exotic topological phase is attracting considerable attention in condensed matter physics and materials science over the past few decades due to intriguing physical insights. As a combination of "topology" and "ferroelectricity, " the ferroelectric (polar) topological structures are a fertile playground for emergent phenomena and functionalities with various potential applications. Herein, the review starts with the universal concept of the polar topological phase and goes on to briefly discuss the important role of computational tools such as phase‐field simulations in designing polar topological phases in oxide heterostructures. In particular, the history of the development of phase‐field simulations for ferroelectric oxide heterostructures is highlighted. Then, the current research progress of polar topological phases and their emergent phenomena in ferroelectric functional oxide heterostructures is reviewed from a theoretical perspective, including the topological polar structures, the establishment of phase diagrams, their switching kinetics and interconnections, phonon dynamics, and various macroscopic properties. Finally, this review offers a perspective on the future directions for the discovery of novel topological phases in other ferroelectric systems and device design for next‐generation electronic device applications. Abstract : The exotic topological phase attracts considerable attention worldwide. Herein, the current understanding of the polar topological structures in functional oxide heterostructures is summarized, for example, in the PbTiO3 /SrTiO3 superlattice. The important role of computational tools such as phase‐field simulations in designing polar topological phases is highlighted.